Anaphylaxis: Revision of the Brighton collaboration case definition. Issue 15 (6th April 2023) - Gold, Michael S.; Amarasinghe, Ananda; Greenhawt, Matthew; Kelso, John M.; Kochhar, Sonali; Yu-Hor Thong, Bernard; Top, Karina A.; Turner, Paul J.; Worm, Margitta; Law, Barbara
Abstract: The Brighton Collaboration (BC) has formulated a number of case definitions which have primarily been applied to adverse events of special interest in the context of vaccine safety surveillance. This is a revision of the 2007 BC case definition for anaphylaxis. Recently, the BC definition has been widely used for evaluating reports of suspected anaphylaxis following COVID-19 vaccination. This has led to debate about the performance of the BC definition in comparison with those from the US National Institute of Allergy and Infectious Disease/Food Allergy Anaphylaxis Network (NIAID/FAAN) and the World Allergy Organization (WAO). BC convened an expert working group to revise the case definition based on their usual process of literature review and expert consensus. This manuscript presents the outcome of this process and proposes a revised case definition for anaphylaxis. Major and minor criteria have been re-evaluated with an emphasis on the reporting of observable clinical signs, rather than subjective symptoms, and a clearer approach to the ascertainment of levels of certainty is provided. The BC case definition has also been aligned with other contemporary and international case definitions for anaphylaxis.